2010
DOI: 10.1111/j.1365-2036.2010.04272.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time‐of‐day dosing on the pharmacokinetics and pharmacodynamics of dexlansoprazole MR: evidence for dosing flexibility with a Dual Delayed Release proton pump inhibitor

Abstract: SUMMARY BackgroundDexlansoprazole MR is a Dual Delayed Release proton pump inhibitor formulated to extend the duration of acid suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
(44 reference statements)
0
31
0
8
Order By: Relevance
“…In this study, patients were to take the study drug in the morning, without regard to food. Comparable acid suppression with dexlansoprazole MR dosing has been demonstrated regardless of the timing of food intake (fasting, before or aft er breakfast) ( 34 ) or the time of day (before breakfast, lunch, dinner, or evening snack) ( 35 ). Although additional studies are needed to assess the impact of various dosing timings of dexlansoprazole MR on GERD symptoms, it is not unreasonable to suggest that increased fl exibility in administration, and therefore increased compliance, would lead to reduced symptoms, particularly at night.…”
Section: Esophagusmentioning
confidence: 99%
“…In this study, patients were to take the study drug in the morning, without regard to food. Comparable acid suppression with dexlansoprazole MR dosing has been demonstrated regardless of the timing of food intake (fasting, before or aft er breakfast) ( 34 ) or the time of day (before breakfast, lunch, dinner, or evening snack) ( 35 ). Although additional studies are needed to assess the impact of various dosing timings of dexlansoprazole MR on GERD symptoms, it is not unreasonable to suggest that increased fl exibility in administration, and therefore increased compliance, would lead to reduced symptoms, particularly at night.…”
Section: Esophagusmentioning
confidence: 99%
“…42 There were no clinically meaningful delays to the absorption of dexlansoprazole when dexlansoprazole was administered before lunch, dinner, or an evening snack compared with administration before breakfast, and there were no apparent differences in systemic exposure, with all regimens being pharmacokinetically bioequivalent (Fig. 4).…”
Section: Clinical Benefitsmentioning
confidence: 99%
“…Additionally, no clinically meaningful differences have been found when taking dexlansoprazole at different times of the day relative to food (fasted or fed conditions), indicating that it can be taken without regard to food or timing of meals. 41,42 A comparison of single-dose dexlansoprazole 60 mg with esomeprazole 40 mg found that at 0-24 hours post-dose, the mean percentage of time with pH > 4 was 58% and 48%, respectively (P = 0.003), and the average mean pH values were 4.3 and 3.7, respectively (P < 0.001). 40 At > 12-24 hours post-dose, dexlansoprazole resulted in greater mean percentage of time with pH > 4 and average mean pH than esomeprazole (60% versus 42% and 4.5 versus 3.5, respectively; P < 0.001).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Studies in healthy volunteers about the effect of PPIs on GERD symptom control and mucosal healing show differences in efficacy, onset of action, potency, and duration of acid suppression (% of time during which intragastric pH > 4/24 h) (42)(43)(44). At standard doses, PPIs maintain intragastric pH > 4 for 10-14 hours (46); doubling the dose increases control, although 50% subjects will have a drop in nocturnal pH with its related symptoms (45).…”
Section: Clinical Evidencementioning
confidence: 99%